1999
DOI: 10.1021/bi9907330
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of the Interaction between the Major Histocompatibility Complex-Related Fc Receptor and Its Fc Ligand

Abstract: The neonatal Fc receptor (FcRn) transports immunoglobulin G (IgG) across epithelia, providing passive immunity and protecting serum IgG from degradation. For both functions, FcRn binds to IgG at the acidic pH of intracellular vesicles (pH Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 26 publications
6
58
0
Order By: Relevance
“…This is likely because of the increased avidity effects of the dimer, but may also be a requirement for inhibition of the IgG-FcRn complex in vivo. IgG contains two FcRn-binding sites and binds to FcRn in a 2:1 stoichiometry as observed for rat FcRn in solution (23) and by x-ray crystallography (37). More recently, hFcRn dimers have been reported on cell membranes (24).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is likely because of the increased avidity effects of the dimer, but may also be a requirement for inhibition of the IgG-FcRn complex in vivo. IgG contains two FcRn-binding sites and binds to FcRn in a 2:1 stoichiometry as observed for rat FcRn in solution (23) and by x-ray crystallography (37). More recently, hFcRn dimers have been reported on cell membranes (24).…”
Section: Discussionmentioning
confidence: 85%
“…More recently, hFcRn dimers have been reported on cell membranes (24). It has been suggested that this 2:1 stoichiometry may be a critical aspect of FcRn function (23), and therefore, a dimeric ligand for FcRn may best inhibit FcRn function in vivo. Thus, the lack of activity of monomeric SYN1327 in vivo may be due to its weaker affinity for FcRn or its monovalency.…”
Section: Discussionmentioning
confidence: 99%
“…In the cocrystals, a long, repeating oligomeric ribbon with a 2n:n stoichiometry was observed, in which FcRn dimers are bridged by Fc molecules so that every Fc dimer interacts with two receptors (38). Studies also suggested that the 2:1 FcRn-Fc complex is formed in solution, although FcRn is not capable of dimerization in these conditions (28,29). However, in some studies, 1:1 FcRn/Fc stoichiometry was also observed under non-equilibrium conditions (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments showed a 2:1 FcRn/Fc binding stoichiometry (26,28,29), whereas the 1:1 FcRn-Fc complex was also observed in some studies (27,29). A better understanding of these interactions could be helped by generating and using monomeric Fc (mFc).…”
mentioning
confidence: 99%
“…Crystal structures of IgG complexes with Fc␥RIII and of IgE with Fc⑀RI show 1:1 receptor:antibody stoichiometry, with the receptor binding across both heavy chains in the lower hinge (12). In contrast, the crystal structure of Fc␣RI complexed with IgA shows 2:1 stoichiometry (13) as does that of FcRn with IgG (14), with the two receptors binding between the heavy chain constant domains 2 and 3 on each heavy chain. The IgY/receptor interaction could have either stoichiometry; on the one hand, IgY is an orthologue of IgG and IgE, which can both show 1:1 stoichiometry, but on the other hand, the location of the IgY receptor, CHIR-AB1, in the same gene cluster as the IgA and FcRn receptors suggests the possibility of a 2:1 stoichiometry.…”
mentioning
confidence: 99%